CD11b Signaling Prevents Chondrocyte Mineralization and Attenuates the Severity of Osteoarthritis - Ehirchiou, Driss; Bernabei, Ilaria; Chobaz, Véronique; Castelblanco, Mariela; Hügle, Thomas; So, Alexander; Zhang, Li; Busso, Nathalie; Nasi, Sonia (Frontiers in Cell and Developmental Biology, 2020)
Osteoarthritis (OA) is a progressive joint disease that is strongly associated with calcium-containing crystal formation (mineralization) by chondrocytes leading ultimately to cartilage calcification. However, this calcification process is poorly understood and treatments targeting the underlying disease mechanisms are lacking. The CD11b/CD18 integrin (Mac-1 or αMβ2), a member of the beta 2 integrin family of adhesion receptors, is critically involved in the development of several inflammatory diseases, including rheumatoid arthritis and systemic lupus erythematosus. We found that in a collagen-induced arthritis, CD11b-deficient mice exhibited increased cartilage degradation compared to WT control animals. However, the functional significance of CD11b integrin signaling in the pathophysiology of chondrocytes remains unknown. CD11b expression was found in the extracellular matrix and in chondrocytes in both healthy and damaged human and murine articular cartilage. Primary murine CD11b KO chondrocytes showed increased mineralization when induced in vitro by secondary calciprotein particles (CPP) and quantified by Alizarin Red staining. This increased propensity to mineralize was associated with an increased alkaline phosphatase (Alp) expression (measured by qRT-PCR and activity assay) and an enhanced secretion of the pro-mineralizing IL-6 cytokine compared to control wild-type cells (measured by ELISA). Accordingly, addition of an anti-IL-6 receptor antibody to CD11b KO chondrocytes reduced significantly the calcification and identified IL-6 as a pro-mineralizing factor in these cells. In the same conditions, the ratio of qRT-PCR expression of collagen X over collagen II, and that of Runx2 over Sox9 (both ratio being indexes of chondrocyte hypertrophy) were increased in CD11b-deficient cells. Conversely, the CD11b activator LA1 reduced chondrocyte mineralization, Alp expression, IL-6 production and collagen X expression. In the meniscectomy (MNX) model of murine knee osteoarthritis, deficiency of CD11b led to more severe OA (OARSI scoring of medial cartilage damage in CD11b: 5.6 ± 1.8, in WT: 1.2 ± 0.5, p < 0.05, inflammation in CD11b: 2.8 ± 0.2, in WT: 1.4 ± 0.5). In conclusion, these data demonstrate that CD11b signaling prevents chondrocyte hypertrophy and chondrocyte mineralization in vitro and has a protective role in models of OA in vivo.